2009
DOI: 10.1080/09637480903018816
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on the flavonoid content and antioxidant capacity ofCitrus hystrixleaf

Abstract: The objective of the present study was to compare fresh (F) use and the effects of boiling (B) and deep-fat frying (DF) on the leaf of Citrus hystrix on total phenolic content, the types and amounts of flavonoids and their total antioxidant capacities (TAC), as measured by three different assays: oxygen radical absorption capacity, ferric reducing/antioxidant power, and scavenging effect on the 2,2-diphenyl-1-picrylhydrazyl free radical. Boiling decreased TAC values on the three assays. The amount of total fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…Moreover, isorhamnetin was identified by MPLC and NMR. This flavonol was previously reported in several Citrus such as C. limon, C. hystrix and C. paradisi (Butryee, Sungpuag, & Chitchumroonchokchai, 2009;Horowitz & Gentili, 1960;Maier & Metzler, 1967).…”
Section: Phytochemical Analysis Of Flavonoid-rich Extract From C Medmentioning
confidence: 70%
“…Moreover, isorhamnetin was identified by MPLC and NMR. This flavonol was previously reported in several Citrus such as C. limon, C. hystrix and C. paradisi (Butryee, Sungpuag, & Chitchumroonchokchai, 2009;Horowitz & Gentili, 1960;Maier & Metzler, 1967).…”
Section: Phytochemical Analysis Of Flavonoid-rich Extract From C Medmentioning
confidence: 70%
“…Lemon (C. limon) and kaffir lime (C. hystrix) are the main species used for these purposes, although a variety of other exotic citrus species are also employed (Butryee et al, 2009). Limited quantities of citrus leaves are imported for flavouring food.…”
Section: Entry Pathway Viii: Other Citrus Plant Parts: Leavesmentioning
confidence: 99%
“…This is probably related to phenolic acids dissolved in vacuoles, and the apoplast determines softening and breaking of cellular components with the consequent release of these molecules into the boiling water in cooking of vegetables 30 . The increased softening property observed in our boiled sample explains the loss of phenolics in comparison with the fresh and fried sample 12 . Moreover, our study showed that the freeze-drying technique did not affect phenolic content in the sample.…”
Section: Discussionmentioning
confidence: 87%
“…Thai food is rich in herbs and spices such as makrut lime leaves which contain a large quantity of polyphenols 10 . Bioactive compounds previously identified in Citrus hystrix include glyceroglycolipids 11 , flavonoids 12 , and α-tocopherol 13 . The leaf of C. hystrix (Rutaceae) is commonly used as a condiment in various Thai dishes especially in sweet green curry (kaeng khieow waan) and the popular sour and spicy shrimp soup (tom yam kung) (boiled processing), khao yam (raw), and herbal fried bean (fried processing).…”
Section: Introductionmentioning
confidence: 99%